AUV planning and calibration method considering concealment in uncertain environments - Wang, Can; Cheng, Chensheng; Yang, Dianyu; Pan, Guang; Zhang, Feihu (Frontiers in Marine Science, 2023)
Autonomous underwater vehicles (AUVs) are required to thoroughly scan designated areas during underwater missions. They typically follow a zig-zag trajectory to achieve full coverage. However, effective coverage can be challenging in complex environments due to the accumulation and drift of navigation errors. Possible solutions include surfacing for satellite positioning or underwater acoustic positioning using transponders on other vehicles. Nevertheless, surfacing or active acoustics can compromise stealth during reconnaissance missions in hostile areas by revealing the vehicle's location. In this paper, we propose calibration and planning strategies based on error models and acoustic positioning to address this challenge. We deploy acoustic markers via surface vessels to reduce navigation errors while maintaining stealth. We present a novel path-planning method for complete-area coverage by AUVs using an unscented Kalman filter and acoustic positioning. By analyzing the statistics of accumulated sensor errors, we optimize the positions of acoustic markers to communicate with AUVs and achieve better coverage. AUV trajectory concealment is achieved during detection by randomizing the USV navigation trajectory and irregularizing the locations of acoustic marker. Simulations based on large-scale maps demonstrate the effectiveness and robustness of the proposed algorithm.